2023
DOI: 10.1021/acs.joc.3c00385
|View full text |Cite
|
Sign up to set email alerts
|

Robust Zinc(II)porphyrin Catalyst for Visible Light Induced C–H Arylation of Heteroarenes

Abstract: Zinc(II)porphyrin catalyzed light induced C−H arylation of heteroarenes from anilines is discussed. The method is nontoxic and efficient, using only 0.5 mol % of porphyrin catalyst to produce bi(hetero)aryls in good yields. This work demonstrates the potential use of porphyrin photocatalysts as efficient and robust alternatives to organic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…Gupta and colleagues accomplished CÀ H arylation of heteroarenes using zinc-coordinated carbazole-linked porphyrin-based photoredox catalysts (Zn-porphyrin) (Figure 21, Table 1L). [43] This work exemplified the concept with 28 instances of various substituted aryl amines, as well as pyrrole, furan, and thiophenes. They found that the substrates containing electron-donating group exhibited reduced reactivity when compared with those containing electron-accepting groups.…”
Section: Examples Of Direct Photoredox Catalysis Via Oxidative Quench...mentioning
confidence: 98%
“…Gupta and colleagues accomplished CÀ H arylation of heteroarenes using zinc-coordinated carbazole-linked porphyrin-based photoredox catalysts (Zn-porphyrin) (Figure 21, Table 1L). [43] This work exemplified the concept with 28 instances of various substituted aryl amines, as well as pyrrole, furan, and thiophenes. They found that the substrates containing electron-donating group exhibited reduced reactivity when compared with those containing electron-accepting groups.…”
Section: Examples Of Direct Photoredox Catalysis Via Oxidative Quench...mentioning
confidence: 98%
“…13–17 A significant breakthrough was made by König and co-workers, who reported light-driven direct C–H arylation of heteroarenes with aryl diazonium salts by employing eosin Y as a photocatalyst in DMSO. 18 Subsequently, this transformation was accomplished with [Ir(ppy) 2 (bpy)]PF 6 , 19 9,10-dihydro-10-methylacridine (AcrH 2 ), 20 CpMn(CO) 3 , 21 bismuthene, 22 pnictogen bismuth (Bi), 23 black phosphorus, 24 molybdenum disulfide, 25 and zinc ( ii ) porphyrin 26 as the photocatalysts. Despite indisputable advances, the use of high-cost unrecoverable transition metal complexes, the poor optical stability of organic dyes, and the use of ultraviolet irradiation have limited practical application.…”
Section: Introductionmentioning
confidence: 99%